2014
DOI: 10.1111/jnu.12093
|View full text |Cite
|
Sign up to set email alerts
|

Honorary and Ghost Authorship in Nursing Publications

Abstract: If nursing scholarship is to maintain integrity and be considered trustworthy, and if publications are to be a factor in professional advancement, editors, nursing leaders, and faculty need to disseminate and adhere to ethical authorship practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…Questionable authorship practices—including the prevalence of honorary and ghost authorship—in leading peer‐reviewed nursing and midwifery journals are a significant threat to the integrity of nursing and midwifery scholarship and research (Johnstone, ; Kennedy et al., ). In a study into honorary and ghost authorship in high‐impact medical journals, Kennedy et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Questionable authorship practices—including the prevalence of honorary and ghost authorship—in leading peer‐reviewed nursing and midwifery journals are a significant threat to the integrity of nursing and midwifery scholarship and research (Johnstone, ; Kennedy et al., ). In a study into honorary and ghost authorship in high‐impact medical journals, Kennedy et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a study into honorary and ghost authorship in high‐impact medical journals, Kennedy et al. () found that the prevalence of inappropriate authorship attribution was 42% for honorary authors and 27.6% for ghost authorship. Reasons for these practices included poor awareness of the rules of authorship, the need for ethical practice to be debated and promoted and power relations between team members (Kennedy et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Kennedy et al (2014), the researchers sent surveys to authors of articles published in 10 nursing journals over 3 years. The study found that 42% of the articles had honorary authors, and 27.6% had ghost authors.…”
Section: Maureen Anthony Phd Rnmentioning
confidence: 99%
“…An analysis of ghost and honorary authorship among articles published within six leading medical journals (e.g., JAMA, The Lancet) in 2008 found that, although there appeared to have been a decrease in ghost authorship, specifically over the previous decade, the prevalence of articles with honorary and/or ghost authorship was still 21% (Wislar et al, 2011). Within 10 top peer-reviewed nursing journals, an even greater number (42%) of articles published in a twoyear period contained honorary authors, and 27.6% had ghost authors (Kennedy et al, 2014). Undeserved authorships; failure to credit collaborating authors; relaxed policies for students, research assistants, and postdoctoral fellows; and an excessive number of co-authors are all serious problems.…”
Section: Introductionmentioning
confidence: 99%